Study of Berseem Hay and Green Berseem on Growth Performance of Post-Weaned Kundhi Buffalo Calf - Muhammad Ijaz,; Ghulam Murtaza Lochi,; Gulfam Ali Mughal,; Abdul Haseeb,; Asad Ali Khaskheli,; Saqib Bijarani,; Feroza Soomro,; Athar Ali Khan,; Shahnawaz Kumbhar ,; Ghulam Mujtaba Lochi, (Journal of Basic & Applied Sciences, 2018)
Sixteen calves were randomly allocated into two treatment groups, i.e. group A and B and were given a transition period from 6th to 8th week. Group A and B were offered with ad libitum berseem hay and green berseem respectively. A calf starter ration was offered ad libitum to both the groups. This study remained continued from 9th to 14th week of the age of the calves (six weeks). The results showed that the final mean value of body weight of group A (76.49±1.36 kg/calf) was significantly higher (P<0.05) than that of group B (72.41±1.38kg/calf). Mean feed conversion ratio (FCR) of group A (2.74±0.22 kg/kgBW) was significantly lower (P<0.05) than that of group B (6.95±0.63 kg/kgBW). Average consumption of berseem of group A (3.32±0.25 kg/day) was significantly lower (P<0.05) than that of group B (11.67± 1.023kg/day). Average consumption of calf starter ration (CS) of group A (7.5 ±0. 5223 kg/day) and group B (8.18±0.51kg/day) were non-significant (P>0.05). Average consumption of water of group A (49.56± 2.937 liter/day) was significantly higher (P<0.05) than that of group B (38.47±2.1178 liter/day). The generated income per calf of group A and group B was Rs. 22716.2/calf and Rs. 21060/calf with net profit of Rs. 3852.05/calf and Rs. 2157/calf, respectively. These figures showed that the calves in group A gave Rs. 1695.5/calf more net profit as compared to the calves of group B. It was concluded from this study that calves fed on berseem hay were more economical to rear and gave more profit as compared to the calves fed on green berseem.